Strength and Morphology of Clayey Seabeds Subjected toSurface-Breaking Pipe Oscillations - Fauzan, Sahdi; Zhechen, Hou; Fraser, Bransby; Phillip, Watson; Christophe, Gaudin (American Society of Civil Engineers, 2025)
The dynamic interaction between subsea cylindrical structures, such as pipelines, risers, and power cables, and the seabed, often composed of fine-grained sediments, can significantly alter seabed soil strength and morphology. These changes impact the fatigue life of risers and offshore renewable energy cables and affect the as-laid embedment of pipelines. This paper presents an experimental study designed to explore these interactions. The study involved subjecting a model pipe, representing subsea pipelines, risers, and cables, to vertical oscillations into and out of reconstituted kaolin clay samples with varying water contents and strengths. Post-test T-bar and water content measurements (taken in the footprint of the pipe test) reveal that water entrainment reduced the soil strength below the remolded strength. Additionally, morphological changes such as trenching and mound formation were observed. This study quantifies the impact of factors such as pipe geometry, cyclic amplitude, pipe–soil failure mechanism, and remolded soil strength on seabed soil strength and morphology.